PEMBERDAYAAN KELOMPOK NELAYAN KUB SEGARA GUNA BATU LUMBANG DENPASAR MELALUI OPTIMALISASI PAKAN ALTERNATIF DAN MANAJEMEN PEMELIHARAAN UNTUK MENINGKATKAN BUDIDAYA KAKAP PUTIH SISTEM KERAMBA JARING APUNG - Wiradana, Putu Angga; Rahayu, Prastyadi Wibawa; Suryantari, Eka Putri; Hanipa, Petronela; Kusuma, Nathania Eka Putri; Matilda, Yuliana (Universitas Mataram, 2025)
In aquaculture, using sustainable feed, especially feed produced from fishery waste, is an effective strategy for improving fish production performance and reducing disease susceptibility. Protein sourced from yellowfin tuna offal, bones, and by-products can be processed into fish protein hydrolysate in the form of fish meal. This raw material can then be used to produce alternative feed products. These products have economic value and can reduce the production costs of feed for white snapper fish farming among partner communities. Based on observations, the priority problems faced by the KUB Segara Guna Batu Lumbang fishermen group in their white snapper cultivation are: the suboptimal availability of independent feed, a lack of periodic water quality measurement, and low white snapper production performance. This community service program (PKM) aims to improve the knowledge and skills of the fishermen group in white snapper cultivation management through training in feed production, water quality monitoring, and production performance analysis. The PKM activities will be carried out from July to August 2025 at the Batu Lumbang Mangrove Ecotourism in Denpasar. Education will be provided through lectures and workshops, and partners' understanding will be measured through pre-tests and post-tests. The success of the program will be evaluated to determine if the activities of making alternative feed based on fishery waste, water quality management, and production performance analysis can significantly improve the partners' knowledge and skills (p≤0.05). This PKM program can contribute to achieving the Sustainable Development Goals (SDGs), specifically Goal 2 (Zero Hunger), Goal 12 (Responsible Consumption and Production), and Goal 14 (Life Below Water). Furthermore, this program aligns with the Government Program's Asta Cita Point 2, which aims to encourage national independence through food self-sufficiency sourced from the fisheries sector and to support a sustainable blue economy.